Essentials of Mo+6/Mo+4 and Ce+4/Ce+3 redox couples in auto-regenerated catalyst for dry methane reforming - Panda, Satyajit; Singh, Gaje; Kaishyop, Jyotishman; Gazi, Md Jahiruddin; Mule, Harshada Mahadev; Khan, Tuhin Suvra; Sharma, Ojasvi; Bordoloi, Ankur (Chemical Engineering Journal, 2025)
Biogas is a potential renewable carbon resource, and dry reforming is one of the promising routes to mitigate via generating syngas, used as a building block for the synthesis of chemicals and fuels. Coke deposition and metal sintering of the reported catalyst systems are the major challenges to developing an economically feasible dry reforming process. Molybdenum oxide is a versatile material with properties like oxygen storage, oxygen mobility, and sulphur tolerance. Here, an oxygen storage capacity enhanced catalyst has been designed by applying a mono layer molybdenum oxide on ceria-magnesia-modified alumina support using a unique chemical vapor deposition method. The Ru and Ni used as active components, and Gd as a promoter were dispersed over the modified support via a precipitation-deposition approach. The most efficient composition is found to be 4 % Ni, 0.5 % Gd, and 0.5 % Ru with Mo-promoted modified alumina with excellent stability up to 500 h for dry reforming reaction studies. Two redox cycles (Mo+6 to Mo+4 & Ce+4 to Ce+3) facilitated a significant number of oxygen vacancies, to limit surface carbon accumulation and support high catalytic stability and activity. The possible reaction pathways and stable surface intermediates were identified by using in-situ DRIFT studies, which included metal carbonyls, carboxylate species, and surface hydroxyl groups. Moreover, the DRIFT studies were supported with CH4-TPSR analysis and DFT studies evidence the formation of CHx species and subsequent oxidation. The additional advantage of the usage of molybdenum is the excellent S-tolerance capacity, which is fully scrutinized experimentally as well as theoretically.
Keywords: and Methane reforming; Coke resistant; Oxygen storage; Redox couple cycles; Sulphur tolerance